Efficacy of PD-1 inhibitor with neoadjuvant chemotherapy in hypopharyngeal and oropharyngeal cancer - Liu, Xue-Ying; Shang-guan, Han-jing; Zhang, Wei (Frontiers in Oncology, 2024)
ObjectiveThis study is aimed to evaluate the efficacy and safety of PD-1 inhibitors combined with neoadjuvant chemotherapy in patients with locally advanced hypopharyngeal and oropharyngeal cancer prior to surgical resection.MethodsThis retrospective analysis included 42 patients diagnosed with locally advanced hypopharyngeal and oropharyngeal cancer. The efficacy, safety, survival, and laryngeal preservation rate were evaluated.ResultsA total of 42 patients were included in this retrospective analysis, of whom 28 had hypopharyngeal cancer and 14 had oropharyngeal cancer. Of the 42 patients, 14 (33.3%) achieved a pathological complete response (PCR) at the primary site, 20 (47.6%) achieved a major pathological response (MPR), and 8 (19%) had an incomplete pathological response (IPR) at the primary lesion. A PCR at both the primary site and the neck lymph nodes was observed in 9 patients (21.4%). The laryngeal preservation rate was 92.9% (26/28) in patients with hypopharyngeal cancer. The median follow-up time was 10.5 months. The median progression-free survival (PFS) was 26.42 months (95% CI, 23.416–29.424), and the median overall survival (OS) was 27.1 months (95% CI, 24.316–29.884). The 1-year PFS rate was 83.1%, and the 1-year OS rate was 85.9%.ConclusionCombination therapy with PD-1 inhibitors and neoadjuvant chemotherapy has demonstrated superior efficacy and safety as a preoperative treatment for locally advanced hypopharyngeal and oropharyngeal cancer. Notably, this treatment regimen does not increase the risk of severe postoperative complications and has shown promising results in improving laryngeal preservation rates.